Interdisciplina y educación superior Una visión desde la salud y las ciencias sociales - Leiva Sandoval, Paula; Jorquera, Sylvia; Blest, Alberto (Ariadna Ediciones, 2023)
The Faculty of Health and Social Sciences of the University of the Americas, since 2020 has been developing a deep process of reflection regarding its foundations and options epistemological, in order to provide an alternative professional training situated and in in tune with the great processes that the country is experiencing. It is within this framework that, during the second half of 2021, a series of instances of academic updating, in relevant topics for the formative work that is developed daily. One of these instances was the "Interdiscipline and University Curriculum" Workshop, in which academics from the Faculty participated. As the final challenge of the workshop, the idea arose to carry out an experience of interdisciplinary collective work, which would allow us to continue strengthening the academic production of the Faculty. In this sense, it is that a group of academics set themselves the task of writing each one a text in relation to the concepts: Human Well-being- Social Transformation- Human Rights- Tolerance-Care-Development, which emerge from the Mission and Vision of the Faculty. addressing them from the disciplinary and professional perspectives, which are at the base of the careers that make up the academic unit. What is presented in this book accounts for the reflections of academics on the Interdiscipline and the different views of the same phenomenon, which come together in the formative task that It is shared daily in the classrooms.